Comparison between histopathologic features of leprosy in reaction lesions in HIV coinfected and non-coinfected patients - PIRES, Carla Andréa Avelar (2015)
BACKGROUND: Leprosy and HIV are diseases that have a major impact on public health in Brazil. Patients coinfected with both diseases, appear to be at higher risk to develop leprosy reactions. OBJECTIVE: The aim of this study is to describe the histopathological aspects of cutaneous lesions during reactional states in a group of patients with HIV-leprosy coinfection, compared to patients with leprosy, without coinfection. METHODS: Two groups were established: group 1 comprised of 40 patients coinfected with HIV-leprosy; group 2, comprised of 107 patients with leprosy only. Patients presenting reactional states of leprosy had their lesions biopsied and comparatively evaluated. RESULTS: Reversal reaction was the most frequent feature in both groups, with dermis edema as the most common histopathological finding. Giant cells were seen in all group 1 histopathological examinations. Dermis edema was the most common finding in patients with erythema nodosum leprosum. CONCLUSION: Few histopathological differences were found in both groups, with reversal reaction as the most significant one, although this fact should be analyzed considering the predominant BT clinical form in the coinfected group and BB form in the group without HIV. Larger prospective studies in patients with HIV-leprosy coinfection are needed to confirm and broaden these results.